Training of Decentralized Muscular Constriction with Restrictive Resistances in Improving the Efficiency of Real-time Propulsion and Upgrading and the Achievement of High Jump for Young - Jebur Al-Majidi, Abdulrazzaq; Al Fadhly, Sareeh; Saleh Fathi, Rafia (International Journal of Psychosocial Rehabilitation, 2020)
The high jump activity abounds in many difficult and complex technical stages that require observance of mechanical conditions and mastery of them to serve the kinematic paths, and this requires searching for auxiliary means related to technical performance to have an impact in the integration of these mechanical conditions for the stages of this event to improve the level of performance of the jumpers of this effectiveness. The importance of the research lies in the training of force by the decentralized contraction with restricted resistances when the working muscle is prolonged by the preparatory conditions and showing its effectiveness to increase the force push and its efficiency in terms of the angle of flight and the change of linear momentum and strengthening the link between the last step Rh and upgrading so as to contribute to the development of the level of mastering and streamline the performance of these stages according to the mechanical performance. The researchers hope to clarify the role of these exercises’ law of impulse intraday to improve the achievement of the youth bouncers’ efficiency. The researchers used the experimental method and applied the research to a sample of high jump champions. They used kinematic analysis and video imaging to measure some of the mechanical variables for the end-of-approach and push-and-end variables, and training for the decentralized contracting of the preparatory positions using rubber ropes and the translator device was applied as resistors of these conditions that could contribute to the development of mechanical conditions related to the stages of approaching and upgrading the high jump and included 32 units, with 4 training units per week. The researchers concluded that the exercises affected the development of the starting variables, the flight angle, and the moment-to-moment efficiency, and a result of them was an evolution in the achievement of the achievement achieved.